2008
DOI: 10.1002/dvdy.21638
|View full text |Cite
|
Sign up to set email alerts
|

Left‐asymmetric expression of Galanin in the linear heart tube of the mouse embryo is independent of the nodal co‐receptor gene cryptic

Abstract: Only very few left/right asymmetrically expressed genes are known in the mammalian embryo. In a screen for novel factors we identified the gene encoding the neuropeptide Galanin in mouse. At embryonic day (E) 8.5 asymmetric mRNA transcription was found in the left half of the linear heart tube. During heart looping and morphogenesis expression became restricted to the atrio-ventricular (AV) canal, followed by specific staining of the AV-node and AV-rings in the four-chambered heart. Expression was inverted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Furthermore, it was recently suggested that galanin promotes glucose uptake into cardiac muscle of diabetic rats by increasing glucose transporter 4 expression in cardiomyocytes (Fang et al, 2013b). In addition to a role in the central and peripheral regulation of cardiovascular function, galanin is also involved in heart development (Schweickert et al, 2008;Jones et al, 2009). Interestingly, galanin expression decreases during cardiomyocyte differentiation (Beqqali et al, 2006).…”
Section: Heart and Central Cardiovascular Controlmentioning
confidence: 99%
“…Furthermore, it was recently suggested that galanin promotes glucose uptake into cardiac muscle of diabetic rats by increasing glucose transporter 4 expression in cardiomyocytes (Fang et al, 2013b). In addition to a role in the central and peripheral regulation of cardiovascular function, galanin is also involved in heart development (Schweickert et al, 2008;Jones et al, 2009). Interestingly, galanin expression decreases during cardiomyocyte differentiation (Beqqali et al, 2006).…”
Section: Heart and Central Cardiovascular Controlmentioning
confidence: 99%
“…For example, the neuropeptide galanin was shown to be asymmetrically expressed, in a flow-dependent manner, on the left side of the mouse heart anlage. As galanin asymmetry was not detected in Xenopus embryonic heart, this species-specific difference might relate to the much higher complexity of the mammalian fourchambered heart (Schweickert et al, 2008). Galanin might have been co-opted to the Nodal cascade through evolution of Pitx2 binding sites in its promoter, an option that has yet to be tackled experimentally.…”
Section: When Did Organ Asymmetry Evolve?mentioning
confidence: 99%
“…The gene expression differences between the AVC and OFT could also reflect differences in timing of cushion formation, the cells populating these regions, or the cardiogenic lineage giving rise to them. For example, the most differentially expressed gene in the OFT was Isl1 , a marker of the secondary heart field that contributes cells to the OFT and right ventricle [57], while the most highly AVC-specific gene was Galanin , a neuropeptide known to be expressed in the AVC before becoming restricted to AV-node and AV-rings [58].…”
Section: Discussionmentioning
confidence: 99%